Kemampuan Isolat Bakteri Asam Laktat Indigenous untuk Menurunkan Kadar laktosa Yogurt = The Ability of Indigenous Lactic Acid Bacteria to Reduce Lactose in Yoghurt - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The purpose of this study was to investigate the ability of indigenous lactic acid bacteria to reduce lactose in yoghurt. Isolates of lactic acid bacteria from different sources (3 dadih isolates, 2 fecal isolates, and 2 gatot isolates) were used in this study. Two isolates from yoghurt were also examined as references. The results showed that mixed culture Streptococcus thermophilus + Lactobacillus bulgaricus + Streptococcus sp Dad 11 (ST+LB+Dad 11) and S. thermophilus + L. bulgaricus + Lactobacillus sp Dad 13 (ST+LB+Dad 13) had higher ability to highest ability to reduce lactose in yoghurt compared to yoghurt starter (ST+LB).